2014
DOI: 10.1002/jsfa.6639
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of polyphenols and organic acids during the fermentation of apple cider

Abstract: The contents of polyphenols and organic acids were affected by fermentation. Their changing profiles during fermentation process were dependent on the type of phenolic compounds and organic acids studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(78 citation statements)
references
References 32 publications
5
71
1
1
Order By: Relevance
“…Malic acid is one of the most important acids in wild apple fruit . Determined content of malic acid in EW was 777.93 ± 1.99 mg 100 g −1 EW, what was in correlation with the literature data .…”
Section: Resultssupporting
confidence: 87%
“…Malic acid is one of the most important acids in wild apple fruit . Determined content of malic acid in EW was 777.93 ± 1.99 mg 100 g −1 EW, what was in correlation with the literature data .…”
Section: Resultssupporting
confidence: 87%
“…This result was caused by benefit effects of enzyme in cell wall degradation and phenolics extraction (Vázquez et al, ), which was in accordance with the changes of TP content as shown in Table . Moreover, the highest level of rutin was 1,864 μg/L, which was slight higher than apple cider (1,840 μg/L) (Ye et al, ). However, concentrations of EGCG, epicatechin, phloretin (Amahyakume variety) and phlorizin (Jinpingshi variety), altogether accounting for only 2.1–13.56% of the total identified phenolics, presented a slight reduction, probably being triggered by reactions of both oxidation and several polymerization.…”
Section: Resultsmentioning
confidence: 97%
“…The phenolic contents and profile have important effects on the sensory properties of apple ciders, mainly on colour, bitterness, and astringency (Ye et al, 2014). High molecular weight procyanidins in ciders are known to contribute to astringency, whereas the smaller compounds contribute to bitter taste (Lea & Arnold, 1978;Symoneaux, Baron, Marnet, Bauduin, & Chollet, 2014;Symoneaux, Chollet, Bauduin, Le Quéré, & Baron, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the discard of the peel and seeds which are rich in different phenolic compounds (Francini, 2013;Wolfe, Wu, & Liu, 2003). The polyphenolic content of apple juice depends on preparation method, such as possible utilisation of pectinolytic enzymes in order to release phenolic compounds from polysaccharide structures, and following treatments, such as pasteurisation, or fermentation parameters in cider production (Ye, Yue, & Yuan, 2014). Endogenous enzymes, such as polyphenol oxidase, oxidise phenolic compounds in the apple juice and affect the sensory quality of the product (Renard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%